Gel material filling material
By adopting optimized gel filler components, the problem of reducing the tailings sand absorption pathway is solved, high-strength and low-cost tailings sand filling effect is achieved, and the company's sustainable development is promoted.
Patent Information
- Application Number
- CN202411796052.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
With the sluggish shutdown of tailings ponds and the construction industry, the consumption of tailings sand has been reduced, resulting in high cost of tailings sand treatment and reduced consumption, which has seriously restricted the company's sustainable development.
A gel filler is used, and its components include filler G material and tailings sand. By optimizing the proportion of component of the filler G material and the combination of gelling agent, the strength and stability of the gelling material are improved and the filling effect is achieved.
The gel filler can significantly improve the strength and stability of the filler. Compared with cement, the amount used is 30% to 50%, reaching 2 to 3 times the strength of the cement, reducing the filling cost, and improving the early strength of the filler.
Smart Images

Figure CN119613060A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tailings treatment, and in particular to a gel material filler. Background Art
[0002] In the early stage, graded coarse-grained tailings were mainly used to fill underground goafs, and fine-grained tailings were stored in dry piles after filtration. In recent years, with the closure of tailings ponds, fine-grained tailings are mainly combined with local tailings disposal units to make cement additives, bricks, etc. At present, due to the sluggish construction industry, the production capacity of brick factories and cement factories has decreased, the tailings disposal channels have been reduced and the disposal volume has decreased, which has seriously restricted the company's normal and sustainable development. It is urgent to find a solution to tailings. Full tailings filling can consume most of the tailings, thereby achieving the goal of a tailings-free mine.
[0003] At present, China Patent No.: CN201710867442.X discloses a novel composite gel material, which is made of base material, coagulant, thickener, filler and water retainer, and each component is calculated by mass as follows: 10 to 35 parts of base material, 5 to 15 parts of coagulant, 1 to 5 parts of thickener, 1 to 5 parts of water retainer, and 45 to 85 parts of filler. The composite gel material of the present invention improves the fire prevention and extinguishing performance and thermal stability of the gel, especially provides high temperature resistance, and has high curing strength at high temperature, and can be effectively used for coal mine fire prevention and extinguishing.
[0004] CN202311794532.2 A cementing filler containing vanadium-titanium slag and a preparation method thereof, the filler includes: a cementing material and an aggregate, the mass ratio of the gelling material to the aggregate is 1:4, the gelling material includes by weight: 0-30 parts of vanadium-titanium slag, 30-60 parts of slag, 30-42 parts of steel slag, and 10-16 parts of desulfurized gypsum; the aggregate includes vanadium-titanium slag for aggregate and lead-zinc tailings. The preparation method is: the method includes: determining the raw material ratio of the gelling material and the aggregate, wherein the mortar-sand ratio of the gelling material is 1:4; weighing the raw materials according to the above ratio, and grinding them separately until the specific surface area meets the requirements; preparing the gelling material, mixing the raw materials of the gelling material with water, and adjusting the water content to a slurry concentration of 70-80%; mixing the prepared gelling material and aggregate with water under the premise of a mass ratio of 1:4, adjusting the water content to a concentration of 70-80%, and obtaining a cementing filler.
[0005] With the closure of tailings ponds, it is no longer possible to operate new tailings ponds due to policy influence. In recent years, with the downturn in the construction industry, the production capacity of brick factories has decreased; the use of cement additives is limited, the tailings disposal volume is limited, and the cost of this disposal method is relatively high; the comprehensive utilization of fine-grained tailings disposal has become a bottleneck restricting the company's sustainable development. Summary of the invention
[0006] Therefore, in view of the above problems, the present invention proposes a gel filler to solve the above problems.
[0007] To achieve the above object, the present invention adopts the following technical solution: a gel filler, the components of which include:
[0008] Filling G material 6.25-11%, tailings 89-93.75%, wherein the concentration of tailings is 60-72%, wherein: the components of filling G material include the following components:
[0009] Sulphoaluminate clinker 45-50%, alkaline regulator 25-30%, coagulant 10-15%
[0010] 2-8% flow promoter, 2-8% enhancer, further, the coagulant includes a combination of PAM and one or two of aluminum chloride and calcium sulfate, and the component ratio is 1:1-1:4.
[0011] Furthermore, the alkaline regulator is calcium hydroxide or sodium hydroxide in a 1:1 combination.
[0012] Furthermore, the flow-promoting agent is one of magnesium stearate or zinc stearate.
[0013] Furthermore, the reinforcing agent is a combination of one or both of sodium silicate and aluminum silicate, and the component ratio is 1:1-1:4.
[0014] Further, the following components are included:
[0015] The filling material is 11% G material and 89% tailings, wherein the concentration of tailings is 72%. The filling material G material includes the following components:
[0016] Sulphoaluminate clinker 45%, alkaline regulator 30%, coagulant 10%
[0017] Flow promoter 8%, enhancer 7%.
[0018] Further, the following components are included:
[0019] Filling G material 6.25%, tailings 93.75%, wherein the concentration of tailings is 60%, wherein: the components of filling G material include the following components:
[0020] Sulphoaluminate clinker 50%, alkaline regulator 25%, coagulant 15%, flow enhancer 2%, enhancer 8%,
[0021] By adopting the above technical solution, the beneficial effect of the present invention is that the new type of cementitious material can have good encapsulation and solid properties with the company's full tailings, achieve a good filling effect, and has the following advantages:
[0022] Less dosage is used to achieve the same filling strength, and compared with cement, the dosage is reduced by 30% to 50%;
[0023] High strength, the same amount of gelling agent is 2 to 3 times the strength of cement;
[0024] The filling body strength increases rapidly, which is very suitable for layered filling mines with high 3-day strength requirements;
[0025] At low lime-sand ratio, higher strength can be achieved, and the filling cost is extremely low for mines that are subsequently filled;
[0026] Compared with conventional filling glue solids (curing agents), the product performance is more stable. Under the action of the stabilizer, the strength of the filling body of G material increases steadily; the overall effect saves about 20% to 30% of the cost of gelling agent;
[0027] As an important part of cementitious filling mining, filling cementitious materials play an important role in the effective management of goaf and safe mining. Through research, it is found that the cementitious materials are very practical for the company's tailings and can greatly reduce the filling cost. At the same time, with the requirements of reducing the water seepage of filling slurry, improving the underground filling environment, and increasing the early strength of the filling body, new cementitious filling materials such as cement powder will have a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The strength test results of different types of filled G material test blocks of the present invention at various ages are shown;
[0029] Figure 2 These are the filling strength test results at various ages of the present invention. DETAILED DESCRIPTION
[0030] The present invention will now be further described with reference to the accompanying drawings and specific implementation methods.
[0031] This embodiment provides a gel filler, the components of which include:
[0032] Filling G material 6.25-11%, tailings 89-93.75%, wherein the concentration of tailings is 60-72%, wherein: the components of filling G material include the following components:
[0033] Sulphoaluminate clinker 45-50%, alkaline regulator 25-30%, coagulant 10-15%, flow promoter 2-8%, enhancer 2-8%, the coagulant comprises a combination of PAM and one or two of aluminum chloride and calcium sulfate, and the component ratio is 1:1-1:4.
[0034] The alkaline regulator is calcium hydroxide or sodium hydroxide in a 1:1 combination.
[0035] The flow-promoting agent is one of magnesium stearate or zinc stearate.
[0036] The reinforcing agent is one of sodium silicate and aluminum silicate or a combination of the two, and the component ratio is 1:1-1:4.
[0037] Includes the following components:
[0038] The filling material is 11% G material and 89% tailings, wherein the concentration of tailings is 72%. The filling material G material includes the following components:
[0039] Sulphoaluminate clinker 45%, alkaline regulator 30%, coagulant 10%
[0040] Flow promoter 8%, enhancer 7%.
[0041] Includes the following components:
[0042] Filling G material 6.25%, tailings 93.75%, wherein the concentration of tailings is 60%, wherein: the components of filling G material include the following components:
[0043] Sulphoaluminate clinker 50%, alkaline regulator 25%, coagulant 15%
[0044] Flow enhancers 2%, enhancers 8%.
[0045] 1. The experimental test method for filling G material formula is as follows:
[0046] (1) Mold preparation
[0047] The test block is made using a 7.07cm×7.07cm×7.07cm standard triple test mold. To facilitate mold removal, a layer of lubricating oil or engine oil is applied inside the mold in advance.
[0048] (2) Material measurement
[0049] Weigh the filling materials according to the mix ratio requirements, measure the solid materials with an electronic scale, and weigh the tap water with a measuring cylinder.
[0050] (3) Pulping
[0051] Pour the weighed filling material into a mixing container, add weighed water according to the mass concentration requirements, stir it manually and then use a handheld mixer to vigorously stir it to form a uniform filling slurry.
[0052] (4) Test block preparation
[0053] According to the number of test blocks required for each group, the mixed slurry was injected into a 7.07cm×7.07cm×7.07cm standard triple test mold.
[0054] (5) Scraping and demoulding of test blocks
[0055] After the mold is filled, let it settle naturally. After the initial setting (depending on the mix ratio, the time required may be 1 to 2 days), scrape the surface of the test block flat. After the test block initially stands on its own (depending on the mix ratio, the time required may be 2 to 3 days), demolding and curing are carried out.
[0056] (6) Maintenance
[0057] The test blocks after demoulding were cured at room temperature.
[0058] 2) Strength test
[0059] (1) Uniaxial compressive strength test
[0060] The uniaxial compressive strength was measured using a NYL-300D pressure testing machine. Three test blocks were taken for testing at each age. After measuring the bulk density of the three test blocks, their uniaxial compressive strength was measured again, and the average value was taken as the uniaxial compressive strength value of the filling body at that age.
[0061] 3) Test results collation
[0062] (1) After the uniaxial compression test, the uniaxial compressive strength of rock is calculated according to the following formula and the result is recorded with three significant figures. (1)
[0064] Where: ——Uniaxial compressive strength of rock (MPa);
[0065] P——specimen failure load (N);
[0066] A——cross-sectional area of the specimen (mm);
[0067] Test results:
[0068] The strength of different types of G-filled test blocks at different ages was tested. The strength test results are as follows: Figure 1 shown.
[0069] Among them, the filling G material formula is as follows:
[0070]
[0071] according to Figure 1 The experimental results show that the filling G material with better gelling effect on whole tailings is SN5#, while the filling G material with the best gelling effect on graded tailings is SN3#.
[0072] 2. The mix ratio of filling materials is crucial to the quality of filling bodies. In order to study the law of tailings-gelling agent on the physical and mechanical properties of filling bodies and provide reference data for filling station operation, tailings cementing filling mix ratio test was carried out.
[0073] 2.1 Test plan for mix proportion test
[0074] This mix ratio test mainly provides uniaxial compressive strength data of tailings cemented filling mix ratio for filling process, and conducts tests on factors such as aggregate type and lime-sand ratio. The main assessment index is the uniaxial compressive strength of each age (3 days, 7 days, and 28 days). This test uses P.O42.5 cement and filling G material used by mines as cementitious materials, and whole tailings and graded tailings as aggregates, and conducts comprehensive tests on the following factors and levels.
[0075] 2.2 Mix ratio test method
[0076] According to the tailings situation, the optional gelling agent is P.O42.5 cement (as the control group), filling G material, and the aggregates are: whole tailings and graded tailings. The compressive strength and density of the test block at 3 days, 7 days, and 28 days are measured. The test method is as follows:
[0077] 1) Test block preparation and maintenance
[0078] (1) Mold preparation
[0079] The test block is made using a 7.07cm×7.07cm×7.07cm standard triple test mold. To facilitate mold removal, a layer of lubricating oil or engine oil is applied inside the mold in advance.
[0080] (2) Material measurement
[0081] Weigh the filling materials according to the mix ratio requirements, measure the solid materials with an electronic scale, and weigh the tap water with a measuring cylinder.
[0082] (3) Pulping
[0083] Pour the weighed filling material into a mixing container, add weighed water according to the mass concentration requirements, stir it manually and then use a handheld mixer to vigorously stir it to form a uniform filling slurry.
[0084] 4) Test block preparation
[0085] According to the number of test blocks required for each group, the mixed slurry was injected into a 7.07cm×7.07cm×7.07cm standard triple test mold.
[0086] (5) Scraping and demoulding of test blocks
[0087] After the mold is filled, let it settle naturally. After the initial setting (depending on the mix ratio, the time required may be 1 to 2 days), scrape the surface of the test block flat. After the test block initially stands on its own (depending on the mix ratio, the time required may be 2 to 3 days), demolding and curing are carried out.
[0088] (6) Maintenance
[0089] The test blocks after demoulding were cured at room temperature.
[0090] Uniaxial compressive strength test
[0091] The uniaxial compressive strength was measured using a NYL-300D pressure testing machine. Three test blocks were taken for testing at each age. After measuring the bulk density of the three test blocks, their uniaxial compressive strength was measured again, and the average value was taken as the uniaxial compressive strength value of the filling body at that age.
[0092] The test results are as follows Figure 2 shown.
[0093] After the uniaxial compression test, the uniaxial compressive strength of rock is calculated according to the following formula, and the result is recorded with three significant digits.
[0094] 2.3 Mix ratio test results and analysis
[0095] P.O42.5 cement and filling G material are used as gelling agents, and the aggregates are: whole tailings and graded tailings. The compressive strength at 3 days, 7 days and 28 days is measured. The filling strength test results of P.O42.5 cement and filling G material at each age are shown in Figure 2 .
[0096] According to the results of the ratio test:
[0097] 1. If we continue to use graded tailings filling and use filling G material, the G material ash-sand ratio of 1:8 can reach the strength of cement ash-sand ratio of 1:4. Currently, mines use more cement ash-sand ratio of 1:10, with a 28-day strength of 0.91Mpa, which can be fully achieved by using filling G material of 1:15.
[0098] 2. If the filling is changed to full tailings filling and filling G material is used, the requirements of mining for filling body strength can be met, that is, the strength of 1:4 ash-sand ratio is 4Mpa in 28 days, and the strength of 1:10 ash-sand ratio reaches 1Mpa in 28 days.
[0099] Cost Analysis:
[0100] Cost analysis of using cement and G-material: currently cement is 600 yuan / t, G-material is 650 yuan / t, and the impact of cement price increase is not considered for the time being. For full tailings filling, using G-material, when the concentration is 60%, the lime-sand ratio is 1:8, which can achieve the 1:4 cement bonding effect, and the strength after 3 days is 0.47Mpa, which can save about 103.12 yuan / m 3 1:4 lime-sand ratio has a strength of 4Mpa in 28 days; 1:10 lime-sand ratio can achieve a cement bonding effect of 1:6, with a strength of more than 1Mpa in 28 days, which can save about 52.5 yuan / m 3 .
[0101] Comparative analysis:
[0102] In summary, this embodiment can have good encapsulation and solid properties with the whole tailings, achieve good filling effect, and have the following advantages: less dosage, achieve the same filling body strength, compared with cement, reduce dosage by 30% to 50%; high strength, the same amount of gelling agent is 2 to 3 times the strength of cement; the filling body strength increases quickly, which is very suitable for layered filling mines with high requirements for 3-day strength; low ash-sand ratio, it can also achieve higher strength, for mines filled later, the filling cost is extremely low; compared with conventional filling glue solids (curing agents), the product performance is more stable, and the G material has a steady increase in filling body strength under the action of the stabilizer. The overall effect saves about 20% to 30% of the cost of using gelling agent.
[0103] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0104] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A gel filler, characterized in that: Its components include: Filling G material 6.25-11%, tailings 89-93.75%, of which the concentration of tailings is 60-72%; Among them: the components of the filling G material include the following components: Sulphoaluminate clinker 45-50%; Alkaline conditioner 25-30%; Coagulant 10-15% Flow enhancers 2-8%; Enhancer 2-8%.
2. A gel filler according to claim 1, characterized in that: The coagulant comprises a composition of PAM and one or two of aluminum chloride and calcium sulfate, and the component ratio is 1:1-1:
4.
3. The gel filler according to claim 1, characterized in that: The alkaline regulator is calcium hydroxide or sodium hydroxide in a 1:1 combination.
4. The gel filler according to claim 1, characterized in that: The flow-promoting agent is one of magnesium stearate or zinc stearate.
5. The gel filler according to claim 1, characterized in that: The reinforcing agent is one of sodium silicate and aluminum silicate or a combination of the two, and the component ratio is 1:1-1:
4.
6. The gel filler according to claim 1, characterized in that: Includes the following components: Filling G material 11%, tailings 89%, of which the concentration of tailings is 72%; Among them: the components of the filling G material include the following components: Sulphoaluminate clinker 45%; Alkaline conditioner 30%; Coagulant 10% Flow enhancers 8%; Enhancer 7%.
7. The gel filler according to claim 1, characterized in that: Includes the following components: Filling G material 6.25%, tailings 93.75%, of which the concentration of tailings is 60%; Among them: the components of the filling G material include the following components: Sulphoaluminate clinker 50%; Alkaline conditioner 25%; Coagulant 15% Flow enhancer 2%; Enhancer 8%.
Citation Information
Patent Citations
A novel composite gel material
CN107473693B
Cemented filling material containing vanadium-titanium slag and preparation method of cemented filling material
CN117756492A